Interictal Discharges: All Roads Lead to Rome?. Issue 4 (July 2022) - Gupta, Siddharth; Kadam, Shilpa D.
Human Interictal Epileptiform Discharges Are Bidirectional Traveling Waves Echoing Ictal Discharges Smith EH, Liou J-Y, Merricks EM, et al. Elife . 2022;11:e73541. Published 2022 Jan 20. doi:10.7554/eLife.73541 . Interictal epileptiform discharges (IEDs), also known as interictal spikes, are large intermittent electrophysiological events observed between seizures in patients with epilepsy. Although they occur far more often than seizures, IEDs are less studied, and their relationship to seizures remains unclear. To better understand this relationship, we examined multi-day recordings of microelectrode arrays implanted in human epilepsy patients, allowing us to precisely observe the spatiotemporal propagation of IEDs, spontaneous seizures, and how they relate. These recordings showed that the majority of IEDs are traveling waves, traversing the same path as ictal discharges during seizures, and with a fixed direction relative to seizure propagation. Moreover, the majority of IEDs, like ictal discharges, were bidirectional, with 1 predominant and a second, less frequent antipodal direction. These results reveal a fundamental spatiotemporal similarity between IEDs and ictal discharges. These results also imply that most IEDs arise in brain tissue outside the site of seizure onset and propagate toward it, indicating that the propagation of IEDs provides useful information for localizing the seizure focus.